Pemberitaan Injil di Era Digital: Studi Teologi Perjanjian Baru tentang Amanat Agung dan Implementasinya melalui IPTEKS - Edward Nimit Abraham; Matius Kalatiku; Jaminter Ompusunggu (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2025)
This study analyzes the implementation of the Great Commission in the context of the digital era, focusing on the utilization of information technology by the church and gospel ministers. Using a qualitative approach through in-depth interviews, digital observation, and document analysis, the study finds that digital media offers significant opportunities for the expansion of the Christian mission. However, its utilization is still not optimal due to low digital literacy, lack of theological integration, and limited strategies for adequate digital discipleship. The findings suggest that digital ministry requires a strong communication theology foundation, an inclusive relational approach, and clear digital ethics to maintain spiritual depth in ministry. The study also emphasizes that the digital world is part of missio Dei, so the church needs to develop hybrid ministry strategies and dialogical faith communities. Therefore, digitalization is not just a tool, but also a new theological space that demands a deep integration of theology, technology, and pastoral care. In this context, the church must develop a more holistic understanding to face the challenges and opportunities offered by the digital world for a more effective Christian mission.